Дослідження процесу вилучення цінних компонентів з відпрацьованих розчинів виробництва синтетичних алмазів - Гринь, Григорій Іванович; Козуб, П. А.; Синицька, Г. М.; Жердєва, С. Ю. (НТУ "ХПІ", 2009)
In article results of researches of separation of metals-solvents from solutions in manufacture of synthetic diamonds by means of a carbonate of calcium, a hydrocarbonate of ammonium, a carbonate of sodium and a sodium hydrocarbonate are resulted. According to researches the most expedient reagent for division of nitrates of nickel, manganese and iron is defined. Dependences рН a solution from suspension volume substance which besieges and the fulfilled solution are resulted. During researches it was establish, that process sedimentation nickel and manganese connections is influenced by sequence of addition substance which besieges: the fulfilled solution to substance which besieges or substance which besieges to the fulfilled solution. The structure of a deposit which is received in the course of sedimentation by means of a sodium hydrocarbonate is defined.
Keywords: хімічне осадження; розчин; фільтрат; натрій карбонат; синтез